Deficient Lipoxin Synthesis: A Novel Platelet Dysfunction in Myeloproliferative Disorders With Special Reference to Blastic Crisis of Chronic Myelogenous Leukemia - Stenke, Leif; Edenius, Charlotte; Samuelsson, Jan; Lindgren, Jan Åke (BLOOD, 1991)
The capacity to convert exogenous leukotriene A4 to lipoxins (LXs) was investigated in platelet suspensions from patients with myeloproliferative disorders (MPD) (n = 22) and healthy control subjects (n = 14). Platelets isolated from the controls produced mainly LXA4, but also 6(S)-LXA4 and the all-trans isomers of lipoxins A4 and B4, as determined by high-performance liquid chromatography and computerized UV spectroscopy. In comparison to control levels, the mean LX synthesis was significantly lower in platelets from the MPD patients (438.7 ± 62.8 and 157.4 ± 31.2 pmol LXA4 per 109 platelets, respectively; mean ± SEM; P = .0001). Platelets from six of the patients showed a particularly low capacity to produce LXs, resulting in LX levels below the detection limit or less than 7% of mean control levels. Notably, all these patients were in blastic crisis of chronic myelogenous leukemia (CML). This severely deficient LX production was paralleled by a dramatically attenuated conversion of arachidonic acid to 12-HETE (12-hydroxyeicosatetraenoic acid), while the formation of HHT (12-hydroxyheptadecatrienoic acid), a product formed via the prostaglandin endoperoxide synthase pathway, was normal. In addition, longitudinal studies of CML patients showed that blastic metamorphosis was associated with a markedly reduced capability to synthesize LXs, while this capacity improved after retransformation into a second chronic phase. The results reveal deficient LX synthesis as a novel platelet dysfunction in MPD, particularly in blastic crisis of CML in which an essentially abolished 12-lipoxygenase activity may be a general phenomenon.